2000
DOI: 10.1074/jbc.m004976200
|View full text |Cite
|
Sign up to set email alerts
|

Three Loops of the Common γ Chain Ectodomain Required for the Binding of Interleukin-2 and Interleukin-7

Abstract: The common ␥ chain (␥c), a subunit of the interleukin (IL)-2, IL-4, IL-7, IL-9, and IL-15 receptors, contributes to both cytokine binding and subsequent signal transduction. Using a model-based site-directed mutagenesis strategy, we have identified residues of the mouse ␥c extracellular domain that are required for normal ␥c-dependent enhancement of IL-2 and IL-7 binding. One of these sites, Tyr-103, is homologous to key ligand-interacting residues in the growth hormone and erythropoietin receptors, whereas Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…Most strikingly, little specificity is conferred upon the IL-2͞␥ c interface due to the formation of only 2 hydrogen bonds, as opposed to 7 and 10 in the other two IL-2͞IL-2R interfaces. Our structural results also agree well with extensive mutagenesis work on defining the epitopes on ␥ c for various cytokines (25,26,35). Tyr-103 ␥ , Cys-160 ␥ , and Cys-209 ␥ , identified as hot-spot residues in all of the cytokine͞␥ c interfaces, form a hydrophobic patch in the center of the IL-2͞␥ c interface.…”
Section: Figsupporting
confidence: 75%
See 1 more Smart Citation
“…Most strikingly, little specificity is conferred upon the IL-2͞␥ c interface due to the formation of only 2 hydrogen bonds, as opposed to 7 and 10 in the other two IL-2͞IL-2R interfaces. Our structural results also agree well with extensive mutagenesis work on defining the epitopes on ␥ c for various cytokines (25,26,35). Tyr-103 ␥ , Cys-160 ␥ , and Cys-209 ␥ , identified as hot-spot residues in all of the cytokine͞␥ c interfaces, form a hydrophobic patch in the center of the IL-2͞␥ c interface.…”
Section: Figsupporting
confidence: 75%
“…Tyr-103 ␥ , His-159 ␥ , and Leu-208 ␥ together with the disulfide (Cys-160 ␥ -Cys-209 ␥ ) contribute 53% of the buried surface on ␥ c and represent the major binding determinant. The importance of the disulfide bridge was previously appreciated from mutagenesis data (25,26), but its direct involvement in ligand binding was unexpected. With a buried surface area of 72 Å 2 and one hydrogen bond, IL2 is the most critical IL-2 residue that contacts ␥ c in accordance with biochemical data (27).…”
Section: Structure Of Il-2r␣ and Itsmentioning
confidence: 99%
“…The available data about sites of interaction of cytokine receptors with their specific ligands indicated that the loop regions of FNIII domains rather than ␤ strands were the most likely ligand-binding sites (32)(33)(34)(35)(36). An alignment of Ig-like domains was used to predict the ␤ strands and loop regions of the G-CSF-R Ig-like domain.…”
Section: Mutation Of the Predicted Loop Regions Of The Ig-like Domain-mentioning
confidence: 99%
“…The pDC302 expression vector containing the full-length mouse IL-4R␣ (mIL-4R␣) cDNA was described previously (22) (provided by Immunex Corp., Seattle, WA). Site-directed mutagenesis of the m␥ c gene was performed by the QuikChange method (Stratagene, La Jolla, CA), as previously described (17). Mutations were verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Recent structure-function analysis of the mouse ␥ c (m␥ c ) ectodomain by site-directed mutagenesis (17), guided by predictions of theoretical models of the ␥ c structure (18 -20), identified four amino acids of ␥ c that are necessary for binding IL-2 and IL-7 (17). One of these residues, Tyr-103, may be directly involved in IL-2 and IL-7 binding.…”
mentioning
confidence: 99%